Enhancement of cation exchange and glucose binding capacity, flavonoids release and antioxidant capacity of Tartary buckwheat powder with ultrafine grinding - Wang, Xinhui; Zhang, Xue; Zhang, Dongjie (Frontiers in Nutrition, 2023)
The objective of this paper was to study the effects of ultrafine grinding on the cation exchange capacity, glucose binding capacity and in vitro digestion characteristics of Tartary buckwheat powder. The results showed that the cation exchange ability and glucose binding strength of Tartary buckwheat powder, Tartary buckwheat bran powder and Tartary buckwheat core powder increased significantly with the increase of crushing frequency (20, 40 and 60 Hz), and the Tartary buckwheat bran powder was the highest. The results of in vitro digestion showed that ultrafine grinding improved the flavonoid release and antioxidant activity of Tartary buckwheat bran powder in the in vitro digestion process. The correlation analysis indicated that the amount of flavonoids released in digestive fluid was significantly related to antioxidant activity. This study may provide a theoretical basis for improving the physicochemical properties and functions of Tartary buckwheat by ultrafine grinding technology.